Actions Objected at Employees in CSR - Report from the Study = Działania ukierunkowane na pracowników w koncepcji CSR - komunikat z badania - Szelągowska-Rudzka, Katarzyna (Zielona Góra: Faculty of Economics and Management Press)
The study analyzed the essence of the social responsibility of organizations and indicated the areas of actions to which this concept applies in the organizations. Particular attention has been paid to CSR practices objected at employees as key stakeholders of the organization. The purpose of the study was achieved in the form of analysis of CSR practices addressed to employees of the selected organizations in the Pomeranian Voivodeship.
Keywords: społeczna odpowiedzialność przedsiębiorstw; praktyki CRS; norma ISO 26000; praktyki w miejscu pracy; strategia personalna; zarządzanie; corporate social responsibility; CRS practices; ISO 26000 standard; practices at workplace; personal strategy; human resources management (HRM)